1984
DOI: 10.1037/0022-006x.52.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral exercise programs in the management of chronic obstructive pulmonary disease.

Abstract: Patients suffering from chronic obstructive pulmonary disease (COPD) can benefit from exercise; however, noncompliance with exercise is a common problem. In order to increase compliance to an exercise program, we randomly assigned COPD patients to one of five experimental groups: behavior modification, cognitive-behavior modification, cognitive modification, attention control, and no-treatment control. In the experimental groups, the patients participated in six sessions designed to increase their adherence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 24 publications
3
60
0
2
Order By: Relevance
“…That these effects of psychological factors are mediated through motivation and adherence remains speculative, since neither adherence to the medical regimen nor motivation were measured directly in this study. However, this is consistent with evidence from other studies [33].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…That these effects of psychological factors are mediated through motivation and adherence remains speculative, since neither adherence to the medical regimen nor motivation were measured directly in this study. However, this is consistent with evidence from other studies [33].…”
Section: Discussionsupporting
confidence: 81%
“…Where psychological factors contribute to an unfavourable outcome, they are amenable to change, for example using cognitive-behavioural therapy [35,36]. Such therapy has been shown to improve exercise tolerance and subjective well-being among people with chronic obstructive pulmonary disease, and is also likely to improve patients' adherence to their rehabilitation programme [33]. Further work should aim to identify in more detail those psychological factors likely to influence rehabilitation outcomes, and to extend rehabilitation programmes to incorporate interventions focused on these factors.…”
Section: Discussionmentioning
confidence: 99%
“…There is little published information on the relative importance of psychological support, but ATKINS et al [17] found that a much longer rehabilitation programme than that used in the present study, including psychological sessions, was more effective in reducing anxiety than psychological sessions alone. In another large study, SASSI-DAMBRON et al [18] found a significant improvement in the transitional dyspnoea index of MAHLER et al [19] 6 months after treatment, in patients who had received six weekly sessions in which they were taught coping strategies by a psychotherapist, compared with patients who had general education sessions.…”
Section: Discussionmentioning
confidence: 49%
“…Of the control conditions discussed in this paper, no-treatment controls most often produce the largest effect size for experimental treatments, because they are least likely to positively affect the outcome [34]. It might be argued that these control conditions set the bar too low, particularly given that many psychological targets will improve somewhat with almost any intervention [35].…”
Section: Commonly Used Control Conditionsmentioning
confidence: 99%